2020
DOI: 10.3389/fped.2020.00001
|View full text |Cite
|
Sign up to set email alerts
|

Using Deep Learning Algorithms to Grade Hydronephrosis Severity: Toward a Clinical Adjunct

Abstract: Grading hydronephrosis severity relies on subjective interpretation of renal ultrasound images. Deep learning is a data-driven algorithmic approach to classifying data, including images, presenting a promising option for grading hydronephrosis. The current study explored the potential of deep convolutional neural networks (CNN), a type of deep learning algorithm, to grade hydronephrosis ultrasound images according to the 5-point Society for Fetal Urology (SFU) classification system, and discusses its potential… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
50
1
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 70 publications
(59 citation statements)
references
References 22 publications
2
50
1
1
Order By: Relevance
“…Virus antigen can bind to cells, leading to the release of various cytokines. 32 Consiglio et al have recently found different cytokine storms in Kawasaki disease and MIS-C. Lymphopenia and CRP were more pronounced at onset of COVID-19 in children, who later develop fulminant MIS-C. They also found different plasma protein patterns in MIS-C and Kawasaki.…”
Section: Discussionmentioning
confidence: 93%
“…Virus antigen can bind to cells, leading to the release of various cytokines. 32 Consiglio et al have recently found different cytokine storms in Kawasaki disease and MIS-C. Lymphopenia and CRP were more pronounced at onset of COVID-19 in children, who later develop fulminant MIS-C. They also found different plasma protein patterns in MIS-C and Kawasaki.…”
Section: Discussionmentioning
confidence: 93%
“…The natural composition of breast milk is well recognized as the golden standard of infant nutrition [ 1 ] and is associated with long-term health benefits [ 2 , 3 , 4 , 5 , 6 , 7 , 8 , 9 , 10 ]. Studies have shown that exclusive breastfeeding is accompanied by a reduced risk for developing medical conditions during childhood such as gastrointestinal infections (e.g., necrotizing enterocolitis) [ 5 , 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…Renal rSO 2 was measured in a subset of infants using neonatal sensors in both centers wrapped around the posterior-lateral flank right below the costal arch with the tip of the sensor pointing toward the spine ( 17 ). The cerebrorenal oxygenation ratio (CRR), based on rSO 2 , was calculated as an indicator of continued hemodynamic redistribution after birth ( 4 ).…”
Section: Methodsmentioning
confidence: 99%